Going Solo - Dahl, Roland (Penguin Group, 1986)
They didn't think for one moment that they would find anything but a burnt-out fuselage and a charred skeleton; and they were apparently astounded whn they came upon my still-breathing body, lying in the sand near by'In 1938.
Keywords: Juvenile literature-Fiction